2004
DOI: 10.1002/em.20068
|View full text |Cite
|
Sign up to set email alerts
|

PTCH polymorphism is associated with the rate of increase in basal cell carcinoma numbers during follow‐up: Preliminary data on the influence of an exon 12‐exon 23 haplotype

Abstract: After first presentation with a basal cell carcinoma (BCC), patients demonstrate interindividual diversity in the rate of development of further BCCs (number/year of follow-up). The mechanism for this variation is unknown. In this study, we evaluated whether PTCH variants mediate this phenomenon. We used negative binomial regression analysis to identify associations between BCC numbers/year and host characteristics, parameters of exposure to ultraviolet radiation (UVR), and PTCH exon 12(1686) C/T, intron 15(25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
5
13
0
1
Order By: Relevance
“…We selected three frequent SNPs present in the PTCH1 gene: 23,24 exon 23 C>T 3944 , exon 12 C>T 1686 and intron 9 C>T 1336‐135 . Polymorphism C>T 3944 has been associated with breast cancer risk in women using oral contraceptives, 29 and with BCC in relation to population eumelanin–phaeomelanin status 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected three frequent SNPs present in the PTCH1 gene: 23,24 exon 23 C>T 3944 , exon 12 C>T 1686 and intron 9 C>T 1336‐135 . Polymorphism C>T 3944 has been associated with breast cancer risk in women using oral contraceptives, 29 and with BCC in relation to population eumelanin–phaeomelanin status 25 …”
Section: Discussionmentioning
confidence: 99%
“…Somatic mutations in the PTCH1 gene or in one of the components of the SHH signalling pathway contribute to development of BCC and other types of cancers 18–22 . Moreover, recent publications suggest that allelic variation of the PTCH1 gene may also influence genetic susceptibility to BCC 23–26 …”
mentioning
confidence: 99%
“…Further analysis revealed that activating or missense mutations in SMOH, a Hh coreceptor, are present in human basal cell carcinomas and medulloblastomas [63,64]. Additional data now exist suggesting various roles for the Hh pathway in breast, esophageal, lung, pancreatic, and stomach tumors [49,[64][65][66][67][68][69][70][71][72][73]. Thus it appears that the Hh pathway is affected in multiple tumor types.…”
Section: Hhs and Cancermentioning
confidence: 97%
“…One possible explanation could be the genetic susceptibility secondary to ethnic affinity. The genetic factors associated with mBCC, particularly PTCH gene polymorphism,[26] have been investigated in several studies; glutathione S -transferase, cytochrome P450 and TNF polymorphism have been suggested as other genetically determined risk factors for mBCC. [142425]…”
Section: Discussionmentioning
confidence: 99%